The Relationship Between Accuracy of Triage Implementation and Patient Waiting Time in the Emergency Department (ER) - Abdul Rivai Saleh Dunggio; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Triage implementation is an important process in Emergency Department (ER) services to determine the priority of patient care based on the level of emergency. The accuracy of triage implementation greatly affects the efficiency of services and patient waiting time in receiving medical treatment. This study aims to determine the relationship between the accuracy of triage implementation and patient waiting time in the Emergency Department (ER). The study used an analytical design with a cross-sectional approach. The study sample consisted of 70 patients who came to the ER and were selected using a purposive sampling technique. Data were collected through observation and recording of patient medical records. Data analysis used the chi-square test. The results showed that patients with appropriate triage had a faster waiting time than patients with inappropriate triage. The results of the statistical test showed a p value = 0.021 (p < 0.05). It was concluded that there was a significant relationship between the accuracy of triage implementation and patient waiting time in the ER. Keywords: Triage, Patient Waiting Time, Emergency Room, Health Services